POTENSI DAN TANTANGAN PROGRAM SEKOLAH RAKYAT DALAM KONTEKS PENCAPAIAN SDGS PENDIDIKAN DI INDONESIA - Rohani Rohani; Elysa Akbariah; Maisyaroh Maisyaroh; Eva Novaria (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
The achievement of the fourth Sustainable Development Goal (SDG), regarding quality education, in Indonesia is still faced with disparities in accessibility, especially for marginalized groups who are difficult to reach by the formal system. This study focuses on an in-depth analysis of the potential and challenges of the People's School Program as a grassroots initiative to bridge this educational gap. Using a descriptive qualitative approach that integrates literature studies and field observations, the study evaluates the program's effectiveness in providing inclusive education services. The study findings indicate that People's Schools have significant potential to reduce financial barriers and increase independent learning participation by 25%, primarily driven by strong parental support. However, the sustainability of this program is still hampered by funding uncertainty, lack of curriculum standardization, and the qualifications of volunteer teachers who have not been certified. The main conclusion confirms that People's Schools function as a strategic complement to formal education, which requires strengthening legitimacy through cross-sector collaboration between the government and the private sector. In addition, the integration of digital learning technology is recommended as an adaptive solution to overcome geographical barriers and increase graduate competitiveness to achieve equitable and inclusive national education. ABSTRAK Pencapaian Sustainable Development Goals (SDGs) poin keempat mengenai pendidikan berkualitas di Indonesia masih dihadapkan pada disparitas aksesibilitas, khususnya bagi kelompok masyarakat marginal yang sulit terjangkau sistem formal. Penelitian ini berfokus pada analisis mendalam mengenai potensi dan tantangan Program Sekolah Rakyat sebagai inisiatif akar rumput dalam menjembatani kesenjangan pendidikan tersebut. Melalui pendekatan kualitatif deskriptif yang mengintegrasikan studi pustaka dan observasi lapangan, penelitian mengevaluasi efektivitas program dalam memberikan layanan pendidikan inklusif. Temuan studi menunjukkan bahwa Sekolah Rakyat memiliki potensi signifikan dalam mereduksi hambatan finansial dan meningkatkan partisipasi belajar mandiri sebesar 25%, terutama didorong oleh dukungan kuat dari orang tua. Namun, keberlanjutan program ini masih terkendala oleh ketidakpastian pendanaan, minimnya standarisasi kurikulum, serta kualifikasi tenaga pengajar sukarela yang belum tersertifikasi. Simpulan utama menegaskan bahwa Sekolah Rakyat berfungsi sebagai komplemen strategis bagi pendidikan formal yang memerlukan penguatan legitimasi melalui kolaborasi lintas sektor antara pemerintah dan swasta. Selain itu, integrasi teknologi pembelajaran digital direkomendasikan sebagai solusi adaptif untuk mengatasi hambatan geografis dan meningkatkan daya saing lulusan demi tercapainya pemerataan pendidikan nasional yang inklusif.